Evaluation of Hypoglycemic Effect of Momordica charantia Extract in Distilled Water in Streptozotocin-Diabetic Rats - Ayoub, Syed Mudasir; Rao, Suguna; Byregowda, Sonnahallipura Munivenkatappa; Satyanarayana, Mayasandra Laxmikanth; Bhat, Narayana; Shridhar, Narayan Bhat; Shridhar, Pragathi Belagola (Brazilian Journal of Veterinary Pathology, 2013)
Momordica charantia or Bitter Melon, a tropical vegetable, is a common food in Indian cuisine and has been used extensively in folk medicine as a remedy for diabetes. The present study was undertaken to evaluate the hypoglycemic effect of Momordica charantia extract in streptozotocin-induced diabetic rat model for a period of 45 days. The alcoholic extract of Momordica charantia was administered orally at the dose rate of 100 and 200 mg/kg body weight in distilled water and compared with standard oral hypoglycemic drug, glibenclamide. In the study a significant (P≤ 0.001) improvement in the physiological and biochemical parameters such as body weight, hemoglobin concentration, serum glucose, cholesterol and triglyceride levels was observed in Momordica charantia treated rats as compared to diabetic control rats. In Momordica charantia treated rats there was gradual and progressive alleviation of streptozotocin effects with M. charantia at higher dose rate (200 mg per kg body weight), more effective in normalizing the pancreatic endocrinal architecture, improving the number of β-cells and in enhancing the insulin secretion. Immunohistochemistry and special staining revealed improvement in the insulin secretion in Momordica charantia and glibenclamide treated groups.